Ischaemic Stroke and occult cardiac abnormality-A Transthoracic Echocardiography based study - A Khandker , Md Mahabubul; Md Hassanuzzaman, -; Barman , Kanuj K; Sam , Masihuzzaman; PK, Kayasthagir; Rahman, Touhidur; Islam, Mohitul (Bangladesh Journal of Neuroscience, 2014)
Background: Most of the cases of stroke are of ischemic origin. Various cardiac diseases have been shown to increase risk of stroke. Cerebral embolism derived from a diversity of cardiac disorders is responsible for H”20% of ischemic stroke. AF is the most powerful and treatable cardiac precursor of stroke. Cardiac abnormalities are important risk factors for stroke. A cardiac source of thromboembolism must be excluded in patients presenting with a definite embolic occlusion of a peripheral artery, or multiple thromboembolic episodes in diverse anatomical regions. These patients should undergo transthoracic echocardiography initially and transoesophageal echo if image quality is unsatisfactory because of obesity, lung disease or chest deformity. Methods: An descriptive and observational study done in Neurology unit, Chittagong Medical College hospital from January 2007 to December 2007.Patients presented primarily as ischemic stroke was examined to find out prevalence of occult cardiac abnormality and to find out the frequency of different type cardiac abnormality in ischemic stroke through echocardiography. Results: A total number of 265 patients were examined. Different types of cardiac findings, the maximum number are LV hypertrophy (23%) and followed by Diastolic dysfunction (17%), than multiple vulvular disease (8.5%). Small number of other abnormality found but no PFO and mitral valve prolapse identified in this study. In under 30yrs age group of cases all the abnormal findings found are valvular abnormality. They are mitral stenosis (2), multiple valvular disease (2) and mitral regurgitation (1). In 30 – 49 yrs age group different abnormal findings, most of which are also valvular lesions including aortic stenosis(2), multiple valvular disease(2) and mitral regurgitation(1). Intracardiac thrombus found in one case.In e”50- 69 yrs age group of patients, maximum abnormality found is LVH(7) followed by Diastolic dysfunction(4).Maximum abnormality found in e”70 yrs of age group is LVH(3) and next to it is distolic dysfunction(2). Interpretation: Echocardiography may provide important information on the cause of ischemic stroke. Taking into account a low rate of findings with direct impact on evidence-based therapeutic strategies, routine use of echocardiography is not warranted in all patients with stroke. In patients younger than 50 years, echocardiography has higher diagnostic yield and should routinely be performed. Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 84-89